2010
DOI: 10.1002/jssc.201000380
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of rosiglitazone and its metabolites in rat liver microsomal fraction using hollow‐fiber liquid‐phase microextraction for sample preparation

Abstract: A three-phase hollow-fiber liquid-phase microextraction method for the analysis of rosiglitazone and its metabolites N-desmethyl rosiglitazone and ρ-hydroxy rosiglitazone in microsomal preparations is described for the first time. The drug and metabolites HPLC determination was carried out using an X-Terra RP-18 column, at 22°C. The mobile phase was composed of water, acetonitrile and acetic acid (85:15:0.5, v/v/v) and the detection was performed at 245 nm. The hollow-fiber liquid-phase microextraction procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…In this study, the incubation times were: 3, 5, 10, 20, 30, 45 and 60 min (n = 3). Of note is that in a previous stability study, it was confirmed that during this time and temperature, there was no degradation of the analyzed analytes (Calixto and Bonato 2010).…”
Section: Metabolism Kineticssupporting
confidence: 63%
See 2 more Smart Citations
“…In this study, the incubation times were: 3, 5, 10, 20, 30, 45 and 60 min (n = 3). Of note is that in a previous stability study, it was confirmed that during this time and temperature, there was no degradation of the analyzed analytes (Calixto and Bonato 2010).…”
Section: Metabolism Kineticssupporting
confidence: 63%
“…Sample preparation was performed by hollow-fiber liquid-phase microextraction (HF-LPME), according to a method previously developed in our laboratory (Calixto and Bonato 2010). n-octanol, used as extraction solvent, was purchased from Sigma-Aldrich (St. Louis, MO, USA); sodium hydroxide, perchloric acid and hydrochloric acid were obtained from Spectrum (New Brunswick, NJ, USA), Nuclear (São Paulo, SP, Brazil), and Mallinckrodt (Xalostoc, Mexico), respectively.…”
Section: Standard Solutions and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 As an alternative for analysis of MG in water, hollow fiber liquid-phase microextraction (HF-LPME) has the merits of simplicity, efficiency, negligible volume of solvents needed and excellent sample cleaning ability. [16][17][18] HF-LPME could be classified into three-phase or two-phase mode, the former was suitable for pre-concentration of acidic or basic compounds, especially for the sample with complex matrix. In order to make the method more effective and environmental friendly, room temperature ionic liquids (ILs) was introduced to the analyzing system, which possess many significant advantages, such as low vapor pressure, wide range of miscibility with other organic solvents, good thermal stability, moderate dissolvability of organic compounds and dual natural polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Idealmente, o solvente orgânico deve ser compatível com a membrana, imiscível na amostra, estável e ter alto poder de solubilização dos analitos a serem extraídos (CALIXTO; BONATO, 2010). A ISR é um fármaco neutro, com logP 3,7 (SCIFINDER, 2012), portanto, a HF-LPME na configuração "duas fases" é a recomendada.…”
Section: Solvente Orgânicounclassified